Growth and Yield of Tomato as Influenced by Stem Pruning - Das, D R; Rahman, S B; Ehsan, G M A; Rahman, M A (Journal of Environmental Science and Natural Resources, 2025)
An experiment was conducted to investigate the influence of four levels of stem pruning (viz., no pruning, pruning to single-stem, pruning to two-stems and pruning to three-stems) on the growth and yield of three tomato cultivars (viz., Roma VF, Pusa Ruby, and Jessica). Varieties and stem pruning had significant influences, singly and in combination, on most of the characters studied. Considering varieties, the maximum record in plant height, number of fruits per cluster, weight of individual fruit, and fruit yield of tomato were obtained from Roma VF whereas Jessica showed the minimum values. In case of pruning, unpruned plants showed the maximum record in number of leaves per plant, number of flower clusters per plant, and number of flowers per plant whereas plants pruned to two-stems showed the minimum values. Pruning to two-stems, however, showed the maximum values of plant height, the number of fruits per plant, the weight of individual fruit, and fruit yield whereas the minimum values were found in the unpruned plants. Considering the combined treatments, the maximum number of fruits per plant (32.00 cm), weight of individual fruit (49.76 g), and fruit yield (79.61 t/ha) were obtained from Roma VF plants pruned to two-stems whereas the minimum values (19.87 cm, 40.20g, and 39.93 t/ha, respectively) were found in Jassica plants with no stem-pruning. Environ. Sci. & Natural Resources, 14(1&2): 31-36, 2025